POTENSI AKUIFER DAERAH DESA KARANGMOJO KECAMATAN WERU KABUPATEN SUKOHARJO PROPINSI JAWA TENGAH BERDASARKAN DATA GEOLISTRIK - Maulana, Fivry Wellda (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2013)
Karangmojo village, District Weru, Sukoharjo regency Central Java, during the dry season drought range.The purpose of this study was to determine the hydrogeological conditions of the data, so it can be estimated groundwater potential areas prone to dry. Aquifer in the area carefully situations with flow in the aquifer system of the space between the grains, and the nature of its production being keterdapatannya locally - local.The method used is the estimation of subsurface geology using the data obtained geoelectric tools hold value types, geological mapping and hydrogeological mapping.Advance the depth of groundwater in wells dug around the village Weru, depth of groundwater in the face of population ranged dug 11 meters from the local ground level. Based on geophysical data obtained, the maximum volume of 330 m3/day of water obtained on the west and on the west timur1 timur2 178 m3/day.